Weight Management Counseling (WMC)p07 During Primary Care Clerkships: Preceptors Perceived Skills, Attitudes and Frequency of Modeling WMC to Students (P07-001-19) - Ashe, Karen (Curr Dev Nutr, 2019)
OBJECTIVES: The United States Preventive Services Task Force (USPSTF) 2018 guideline for the management of adults with obesity continues to support screening and offering or referring patients with obesity to intensive multi-component behavioral intervention. Training the primary care work force is important for implementation of guidelines. It is unclear to what degree medical school preceptors provide weight management counseling (WMC) training during primary care core clerkships. This study seeks to describe preceptors’ perceived skills and attitudes towards providing WMC to patients and the frequency of preceptors modeling WMC to medical students. METHODS: Primary care preceptors (family/community medicine and ambulatory internal medicine) from medical schools participating in a larger multi-modal curriculum intervention were recruited to participate in an anonymous 10-minute cross-sectional survey on their perceived skills, attitudes, and modeling WMC to medical students. RESULTS: The survey was completed by 77 eligible preceptors (response rate of 33%). Preceptors perceived themselves to be moderately skilled in WMC, with a perceived WMC skills mean of 2.8, sd 0.56 (range 1–4). Their mean attitudes score was 2.1, sd 0.5 (range 1–4). Preceptors agree they have a responsibility to provide WMC and can be effective with patients. Preceptors report sometimes modeling WMC behaviors to medical students, the mean was 3.26, sd 0.48 (range 1–5). Of those preceptors who never/rarely model referrals, the most common reason was lack of resources followed by patient cost barriers. CONCLUSIONS: Preceptors do not consistently model WMC for medical students during primary care core clerkships. Skill perception and resource availability may contribute. FUNDING SOURCES: Research reported in this publication was supported by the National Center for Advancing Translational Sciences of the National Institutes of Health under award number TL1-TR001454. The content is solely the responsibility of the authors and does not necessarily represent the official views of the NIH.